POLITIK HUKUM REGULASI PEMIIHAN UMUM DI INDONESIA: PROBLEM DAN TANTANGANNYA - Diniyanto, Ayon (Jurnal Legislasi Indonesia, 2019)
The holding of general elections or elections is a consequence that must be carried out by democratic countries including Indonesia. Implementation election in Indonesia is always covered by legal instruments. Welcoming election in 2019 the overarching legal instrument is Law Number 7 of 2017 concerning General Elections. The legal instrumen in its situation turns out to have problems. Problem include presidential threshold, parliamentary threshold, electoral system, electoral district of magnitude, and result conversion method. The existence of these problems is certainly a challenge in the implementation of Law Number 7 of 2017 concerning General Elections wich must be faced. Before facing the challenge, it is better to know in advance the legal politics of Law Number 7 of 2017 concerning General Elections. It is very important to know the purpose of making regulations about elections. This article dicusses the legal politics of Law Number 7 of 2017 concerning General Elections usin three criteria, namly (1) legal policies issued; (2) legal policy background; and(3) law enforcement from policies issued. This aricle also reviews the problem and substnace of Law Number 7 of 2017 concerning General Elections as mentioned.